2022
DOI: 10.30598/ijcr.2022.10-lat
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chitosan-Citrate Microparticle Using Ionic Gelation Methods

Abstract: A study has been conducted aimed to synthesize chitosan-citrate using the ionic gelation method and its characterization with FTIR, SEM, SAA, and PSA, as well as solubility and swelling tests. The results showed that chitosan reacted with sodium citrate producing chitosan-citrate particles. The product of chitosan-citrate has a rough and thickened surface morphology. Surface area is obtained by 35.233 m2/g and pore size is 0.027 cc/g, smaller than chitosan. Based on solubility and swelling tests in acidic, alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Alginate is also a natural polymer that has anionic groups (COO -) in its structure so that it can form a polyelectrolyte complex with chitosan, which has cationic groups (NH 3 + ) (Latupeirissa et al, 2022;Sunardi et al, 2021). The previous research from Kulig et al, (2017) showed that the chitosan-alginate polyelectrolyte complex film has better mechanical strength than films made from only one type of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate is also a natural polymer that has anionic groups (COO -) in its structure so that it can form a polyelectrolyte complex with chitosan, which has cationic groups (NH 3 + ) (Latupeirissa et al, 2022;Sunardi et al, 2021). The previous research from Kulig et al, (2017) showed that the chitosan-alginate polyelectrolyte complex film has better mechanical strength than films made from only one type of polymer.…”
Section: Introductionmentioning
confidence: 99%